The menagerie eaudiobook - Sutherland, Tui T. (Menagerie, 2019)
From the New York Times bestselling author of the Wings of Fire series, Tui T. Sutherland, and her sister, Kari H. Sutherland, comes the Menagerie series, perfect for fans of Brandon Mull's Fablehaven series and The Spiderwick Chronicles. In the small town of Xanadu, Wyoming lies the Menagerie, a top secret facility filled with unicorns, dragons, phoenixes, and other fairy tale creatures. At least, it was a secret—until six griffin cubs escaped. If Logan and Zoe don't get the cubs back fast, the entire Menagerie will be shut down. The race is on and the resulting adventure is only the beginning of a thrilling series that will leave readers wanting a magical menagerie of their very own.